Stability analysis of Magnetohydrodynamic flow and heat transfer over an exponentially permeable stretching/shrinking sheet in Ferrofluids with the influence of heat generation - Norshafira, Ramli; Nurul Syuhada, Ismail; Syakila, Ahmad (CRC Press, 2025)
The steady, two-dimensional and laminar magnetohydrodynamic flow and heat transfer over an exponentially permeable stretching/shrinking sheet in ferrofluids with the existence of heat generation and suction is numerically studied. Using appropriate similarity variables, the governing partial differential equations are reduced to ordinary differential equations before being solved by a collocation method, namely the bvp4c function in MATLAB. This investigation explores the influence of parameters involved in this study towards the skin friction coefficient, local Nusselt number, velocity, and temperature profiles, and the results are showed graphically and thoroughly discussed. Interestingly, dual solutions (first and second solutions) exist in this study which prompted us to proceed more with the stability analysis. This analysis revealed that the first solution is stable and physically reliable and the second solution is unstable and not physically reliable. The results show that the upsurge of the magnetic parameter and mass transfer parameter (suction) help boost the heat transfer rate. Moreover, an enhancement in heat transfer rate can be observed as the heat generation parameter decreases.